Myeloid checkpoint blockade improves killing of T-acute lymphoblastic leukemia cells by an IgA2 variant of daratumumab - Baumann, Niklas; Arndt, Christian; Petersen, Judith; Lustig, Marta; Rösner, Thies; Klausz, Katja; Kellner, Christian; Bultmann, Miriam; Bastian, Lorenz; Vogiatzi, Fotini; Leusen, Jeanette H. W.; Burger, Renate; et al. (Frontiers in Immunology, 2022)
Antibody-based immunotherapy is increasingly employed to treat acute lymphoblastic leukemia (ALL) patients. Many T-ALL cells express CD38 on their surface, which can be targeted by the CD38 antibody daratumumab (DARA), approved for the treatment of multiple myeloma. Tumor cell killing by myeloid cells is relevant for the efficacy of many therapeutic antibodies and can be more efficient with human IgA than with IgG antibodies. This is demonstrated here by investigating antibody-dependent cellular phagocytosis (ADCP) by macrophages and antibody-dependent cell-mediated cytotoxicity (ADCC) by polymorphonuclear (PMN) cells using DARA (human IgG1) and an IgA2 isotype switch variant (DARA-IgA2) against T-ALL cell lines and primary patient-derived tumor cells. ADCP and ADCC are negatively regulated by interactions between CD47 on tumor cells and signal regulatory protein alpha (SIRP on effector cells. In order to investigate the impact of this myeloid checkpoint on T-ALL cell killing, CD47 and glutaminyl-peptide cyclotransferase-like (QPCTL) knock-out T-ALL cells were employed. QPTCL is an enzymatic posttranslational modifier of CD47 activity, which can be targeted by small molecule inhibitors. Additionally, we used an IgG2 variant of the CD47 blocking antibody magrolimab, which is in advanced clinical development. Moreover, treatment of T-ALL cells with all-trans retinoic acid (ATRA) increased CD38 expression leading to further enhanced ADCP and ADCC, particularly when DARA-IgA2 was applied. These studies demonstrate that myeloid checkpoint blockade in combination with IgA2 variants of CD38 antibodies deserves further evaluation for T-ALL immunotherapy.